Giant, rapid-growing lipoma of Retzius space - Goran Augustin (Hrvatski liječnički zbor, 2021)
In the 57-year old, healthy postmenopausal female, an asymptomatic suprapubic mass was an accidental finding on a regular gynecologic ultrasound (US). In 50 days, three transabdominal US and computed tomography (CT) scans showed a rapid increase in mass size (from 5.6 x 1.1 cm to 11 x 6 cm to 12.5 x 7 cm on the US, 19 x 11 cm on CT). Previous medical history noted thrombocytopenia (1 x 109/L) and an intrauterine device (IUD) with the hormonal release. The carcinoembryonic (CEA) marker was slightly elevated (4.1 IU/L). Abdominal CT with intravenous contrast revealed encapsulated mass with the intensity of fatty tissue without discernible primary origin. No signs of infiltration and invasion of surrounding structures were found. CT differential diagnosis included lipoma and low-grade liposarcoma. After exploratory laparotomy and complete extirpation of the tumor (24 x 19 x 7 cm) from the Retzius space, the histopathology confirmed a lipoma with negative estrogen and progesterone receptors. The postoperative course was uneventful, and one year after surgery, US and magnetic resonance (MR) imaging did not show recurrence.